The influence of microstructure on the magnetic properties of WC/Co hardmetals - Topic, Irena; Sockel, Hans-Georg; Wellmann, Peter; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2006)
The magnetic properties of conventional and ultrafine-grained WC/Co hardmetals have been measured and related to the microstructure. The microstructure was characterised using scanning electron and atomic force microscopy. The WC grain size was found to vary between 1.0-2.5 and 0.1-0.3 mu m for conventional and ultrafine-grained hardmetals, respectively. In conventional WC/Co hardmetals the coercivity increases as the WC grain size decreases. In the ultrafine-grained hardmetals with the WC grain size below 0.5 mu m, the coercivity was found to increase strongly and be one order of magnitude higher than in the conventional hardmetals. The relationship between magnetic properties and microstructure in this work can be extended to smaller grain sizes and ties in well with literature results. The developed relationship can be used as a quick method to estimate the WC grain size by measuring the magnetic coercivity. Furthermore, it was confirmed that the coercivity is not only a function of grain size, but also of cobalt content. All results lead to the conclusion that an increase in WC-Co interface area increases the coercivity values. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: WC/Co hardmetals; Ultrafine-grained (UFG); WC–Co interface area; Coercivity; Magnetic saturation; Magnetic domains